2021
DOI: 10.1002/jnr.24809
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial role of the synthetic microneurotrophin BNN20 in a focal demyelination model

Abstract: Myelin, produced by oligodendrocytes (OLs) in the central nervous system (CNS) and Schwann cells in the peripheral nervous system (PNS), is an evolutionary trait of vertebrates contributing to action potential propagation over long distances. Myelin disruption occurs in demyelinating diseases and results in the cell death of either OLs or Schwann cells, leading to axonal demyelination and degeneration causing impairments in motor and cognitive function. There is a variety of demyelinating diseases with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Administration of either DHEA or DHEAS significantly reduced the severity, incidence, and neurobehavioral deficits of EAE ( 122 , 124 ). Moreover, a recent study suggested that BNN20, a C17-spiroepoxy derivative of DHEA, could function as a neuroprotective molecule to reduce inflammation by binding to the neurotrophin receptor ( 125 ). The reduction in the levels of DHEA in patients with MS might play a role in facilitating the pathophysiology and progression of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of either DHEA or DHEAS significantly reduced the severity, incidence, and neurobehavioral deficits of EAE ( 122 , 124 ). Moreover, a recent study suggested that BNN20, a C17-spiroepoxy derivative of DHEA, could function as a neuroprotective molecule to reduce inflammation by binding to the neurotrophin receptor ( 125 ). The reduction in the levels of DHEA in patients with MS might play a role in facilitating the pathophysiology and progression of this condition.…”
Section: Discussionmentioning
confidence: 99%